2020
DOI: 10.1002/chem.202002238
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals “Divorce and Marriage”: When a Binary System Meets an Active Multifunctional Synthon in a Ball Mill

Abstract: Aw ell-defineda nd stable "AB" binarys ystem in the presence of "C" ac rystalline synthon ground in ab all mill undergoes selective transformation in the solid state according to the equation AB + C!AC + B. When the amount of Ci si ncreased two times then the equation AB + 2C! AC + BC is valid. The other variants are more complex. The pathway BC + Ai sa llowed and leads to the AC andBproducts. The pathway AC + Bi sn ot preferred, and no transformation is observed. These non-obviouscorrelations were observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Our work complements ongoing developments in the application of fast MAS to pharmaceuticals to show the power of NMR crystallography for characterising the solid-state forms of pharmaceutical molecules. 38,41,43,44,46,58,59,67,109…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work complements ongoing developments in the application of fast MAS to pharmaceuticals to show the power of NMR crystallography for characterising the solid-state forms of pharmaceutical molecules. 38,41,43,44,46,58,59,67,109…”
Section: Discussionmentioning
confidence: 99%
“…32 The 1 H− 1 H DQ MAS NMR experiment has found application to a cysteine-based formulation, 33 the diethylcarbamazine citrate salt which is used in the treatment of filariasis caused by worm infection, 34 the multiple-sclerosis treatment teriflunomide, 35 as well as for identifying differences between crystalline and amorphous indomethacin. 36 Other applications include 15 N-labelled rosette nanotubes, 37 co-crystals formed by ball milling 38 and quartet and ribbon-like self-assemblies. 39 Aromatic pi-pi interactions can also be probed by the 1 H− 1 H DQ MAS NMR experiment, for example in diphenylalanine nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…To answer this question, as a tool of choice we used NMR spectroscopy employing techniques with magic angle sample spinning (MAS). [40] It is widely accepted that solid state NMR spectroscopy is a method of analysis that does not destroy a material, but this does not mean that it is not invasive, especially when performing MAS experiments. Very recently Bartalucci et al have reported that bromination of a heterocyclic sulfoximine in a MAS rotor can be induced using the centrifugal pressure (CeP).…”
Section: Multi-stage Mechanism Of Et:ema Et:glu and Et:mal Cocrystals...mentioning
confidence: 99%
“…[37] Our study focuses on cocrystals of ethenzamide (ET) with three different dicarboxylic acids, all of which can be easily formed by neat mechanochemical grinding or hot-stage melting. [38,39] Another important aspect of understanding cocrystal formation is the exchange of coformers during mechanochemical grinding, observed by us [40] and other research groups, [41][42][43] as well as selectivity towards one product in competitive mechanochemical reactions. [27][28][29] A driving force of such processes can be of thermodynamic and/or kinetic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR can be used to gain insights into crystallographic disorder occurring in bulk pharmaceuticals , and can be combined with gauge-including projector-augmented-wave (GIPAW) calculations to verify and refine the crystal structure, that is, NMR crystallography. ,,, As a technique that observes the bulk sample, solid-state NMR can be used to validate the occurrence of crystallographic disorder and determine its nature. ,, The disorder caused by dynamics can be investigated by solid-state NMR, offering qualitative information through line-shape analysis, chemical shift measurement, and dipolar coupling measurements. , In addition, quantitative information on the thermodynamic parameters of the dynamics can be obtained through relaxation time measurements. ,,, There are limits to the ability of solid-state NMR to investigate disorder, which may arise due to the nature of the technique. Examples of this may arise from an insufficient resolution required to adequately resolve the crystallographic disorder, the disorder involving unreceptive nuclei or potentially missing the presence of dynamics occurring at a timescale distinct from that of the one-dimensional NMR experiment.…”
Section: Introductionmentioning
confidence: 99%